Pengaruh Manajemen Perawatan, Manajemen Docking, Manajemen Logistik Suku Cadang, Manajemen Crew dan Manajemen QHSE Terhadap Operasional Kapal di PT Kartika Samudra Adijaya - Yonathan Arunglabi; Freddy J. Rumambi; Nofrisel Nofrisel (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the factors that influence ship operations, namely maintenance management, docking management, spare parts logistics management, crew management, and QHSE management at PT Kartika Samudra Adijaya. This study uses a quantitative research method with a cross-sectional approach. Data were collected using questionnaires distributed online to 35 ship crew members at PT Kartika Samudra Adijaya. The data analysis method in this study uses partial least squares (PLS) with the assistance of the SmartPls application version 3.0. The results show that maintenance management, docking management, spare parts logistics management, crew management, and QHSE management have a positive and significant effect on ship operations at PT Kartika Samudra Adijaya. The contribution of these five variables is 71.9%, while the remainder is influenced by other variables outside this study.